Low Frequency Experimental Analysis of Dry Friction Damping in Cable Isolators. Issue 4 (December 2015) - Guzmán-Nieto, Michelle; Tapia-González, Pablo E.; Ledezma-Ramírez, Diego F.
Mechanical vibrations normally produce adverse effects in structures, machinery and people. One of the most used methods of vibration control is vibration isolation. Amongst the different configurations of isolators, wire rope springs, also known as cable isolators are used for their high capacities of energy storage and dissipation, which is based on dry friction. As a result, they are used in extreme applications such as aeronautical, military, naval, and others involving high vibration and shock levels. An experimental analysis of the quantification of dry friction damping is presented in this paper, estimating the damping by two methods, namely a low frequency sinusoidal input to obtain the hysteresis loops, then a broadband frequency excitation in order to estimate the modal damping. It is found that there is an optimum value of deflection and load on the springs that produce the highest energy dissipation; a similar trend is observed in the two methods considered. This will give more insight into understanding the mechanism of energy dissipation and use of this information to improve the design of vibration isolators.